2007
DOI: 10.1523/jneurosci.1331-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Correlates of Sentence Comprehension and Verbal Working Memory in Neurodegenerative Disease

Abstract: This study investigates whether sentence comprehension and nonsyntactic verbal working memory (vWM) are sustained by the same or by different neural systems. Scores in a sentence-picture matching task and in digits backward (DB) were correlated with magnetic resonance imaging voxelwise gray matter volumes using voxel-based morphometry in 58 patients with neurodegenerative diseases. Results showed that overall sentence comprehension scores, regardless of grammatical structure, correlated with gray matter volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 73 publications
(93 reference statements)
16
84
0
Order By: Relevance
“…One study associated impaired sentence comprehension with posterior-inferior frontal and anterior-superior temporal regions of the left hemisphere 7. In mixed groups of neurodegenerative patients, grammatical comprehension was related to left inferior frontal atrophy 23 24. The present study found that difficulty understanding cleft sentences in naPPA is related to left anterior-superior temporal GM atrophy.…”
Section: Discussionsupporting
confidence: 51%
“…One study associated impaired sentence comprehension with posterior-inferior frontal and anterior-superior temporal regions of the left hemisphere 7. In mixed groups of neurodegenerative patients, grammatical comprehension was related to left inferior frontal atrophy 23 24. The present study found that difficulty understanding cleft sentences in naPPA is related to left anterior-superior temporal GM atrophy.…”
Section: Discussionsupporting
confidence: 51%
“…This inferior frontal involvement is not unexpected given the presence of agrammatic aphasia in this group and the known association between Broca area and agrammatic aphasia. 29,30 Similarities were also noted with the DTI analysis. In contrast to PPAOS and dominant AOS, the agPPA group showed widespread abnormalities for all imaging modalities.…”
supporting
confidence: 70%
“…To cope with this limitation, the syntactic computational unit may require additional memory resources provided by the LIFS to deal with the partial products of parsing of doubly embedded sentences. Indeed, a recent voxel-based morphometry study found that gray-matter volume reduction in the LIFS correlates with a deterioration in the comprehension of center-embedded sentences (38).…”
Section: Functional Coupling and Structural Connectivity Between The mentioning
confidence: 99%